Analisis Pengendalian Banjir Pada Wilayah Desa Kupa Kabupaten Barru - Fachrezy Putra F; Andi Rumpang Yusuf; Burhanuddin Badrun (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Flooding is a natural disaster event that occurs when excessive water flow inundates the land. In Barru Regency, Kupa Village is a coastal area that includes an area prone to flooding. Flooding in Kupa Village greatly affects traffic where when flooding traffic on the Makassar - Pare-pare axis road is jammed even making cars or motorbikes can break down in the middle of a high puddle, therefore flooding in Kupa Village needs to be studied to find solutions to overcome it. This research was conducted in Kupa Village with the aim of analyzing the amount of rainfall and flood discharge for the return period of 25, 50 and 100 years and analyzing flood control methods. Furthermore, the plan flood discharge analysis was carried out using the HSS Nakayasu method, based on the calculation obtained the 25-year return period flood discharge (Q25) of 238,164/sec, 50-year return period (Q50) of 245,188 /sec, 100-year return period (Q100) of 251,770 /sec. From the analysis of runoff data in Kupa Village is 22.5110945/sec, where if there is a tide up to 1.7 m high along with rain that falls 1-3 hours or more resulting in flooding in the village of Kupa and the results of the analysis for the right building in overcoming flooding in Kupa Village is the installation of embankments around the Makassar - Pare-pare Axis road.